Perancangan Ulang Tata Letak Fasilitas di PT. Dwi Komala dengan Metode Systematic Layout Planning - Naganingrum, R. Pitaloka; Jauhari, Wakhid Ahmad; Herdiman, Lobes (Performa: Media Ilmiah Teknik Industri, 2013)
PT. Dwi Komala is one of middle-scale industries that producing in footwear product. In production system, waste such as movement waste and excessive transportation, are commonly found and affect to unmet production target. This waste occurs because the work station placement does not consider the production process flow and spatial interconnectedness. One of solutions that can be done to repair the facility layout is redesigning the layout by considering production process flow and the relationship between any space in the layout. The layout of facilities in this company is not made based on the good planning but only adjusting with the existing space, so that irregular layout results. Meanwhile, the facility layout not taking into account the production process flow, production machineries placement and production activity requirement results in larger material handling cost and it will impact on the high production cost and production process time. For that reason, this research aims to produce the proposal of layout design that can minimize the material handling cost (MHC). In this research, the facility is redesigned using Systematic Layout Planning (SLP). The SLP procedure consists of three stages: analysis, adjustment and evaluation. The analysis stage includes material flow analysis, activity relationship chart (ARC), activity relationship diagram (ARD), area requirement analysis and available area analysis. The adjustment stage includes planning the spatial relationship diagram and alternative layout design. In evaluation stage, the evaluation was done on the alternative layout design. Three proposed layout which minimizes material handling cost could be resulted by Systematic Layout Planning (SLP) method. The first proposed layout gives a significant saving of 11.35% compare to existing layout. The second layout results in 31.17% saving while the last layout gives a saving of 32.44%. Thus, the third layout proposal was recommended as the selected layout proposal